THE THEORETICAL FEASIBILITY OF SLIDE INTERACTIVE MEDIA BASED POWER POINT OF HEREDITY IN CLASS XII SENIOR HIGH SCHOOL - SULFIAH (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Hereditary is material that is difficult to understand. The material can not be observed with ordinary light microscope, so we need learning media that can provide an illustration of the relevant material to facilitate understanding learners. Many teachers using power point slide that just display pictures / photos and writings in learning, so the motivation of learners to learn the material of heredity is low. The purpose of this study is describing the theoritical feasibility of slide interactive media based power point of heredity in class xii senior high school which is gotten from research result of expert faculty of media, matter expert lecturers and teachers of Biology. This study refers to the ASSURE models. Results showed that slide interactive media based power point developed worthy use in learning by faculty experts and biology teacher with an average score of 3.48 overall worth is included in the category. Keywords: Interactive Slides Media, Microsoft Power Point, Heredity.